Optimum conditions for ascorbic acid determination in three Iraqi citrus using HPLC technique - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
A high-performance liquid chromatography method was employed for the quantitative determination of ascorbic acid (AA) which called vitamin C in three types of Iraqi citrus (orange mandarin and aurantium ) and to establish this goal , evaluation of ascorbic acid degradation is so important due to its significant criticality when exposure to ordinary atmospheric conditions. The chromatographic analysis of AA was carried out after their sequential elution with KH2PO4 ( as mobile phase) by reverse-phase HPLC technique with C8 column and UV detection at 214 nm. .Bad resolutions was appeared clearly for C8 column , so another alternative condition were carried out to improve the resolution by replacement of C8 by C18 column .Statistical treatments were used to calculate relative standard deviation (RSD%) for the results to gain acceptable confidence to the present work , so the linearity of calibration curve, accuracy, and repeatability of this method are all satisfactory.